High suicidality predicts overdose events among people with substance use disorder: A latent class analysis - Schmidt, Renae D.; Horigian, Viviana E.; Shmueli-Blumberg, Dikla; Hefner, Kathryn; Feinberg, Judith; Kondapaka, Radhika; Feaster, Daniel J.; Duan, Rui; Gonzalez, Sophia; Davis, Carly; Vena, Ashley; Marín-Navarrete, Rodrigo; et al. (Frontiers in Public Health, 2023)
Introduction Suicide is the tenth leading cause of death in the United States and continues to be a major public health concern. Suicide risk is highly prevalent among individuals with co-occurring substance use disorders (SUD) and mental health disorders, making them more prone to adverse substance use related outcomes including overdose. Identifying individuals with SUD who are suicidal, and therefore potentially most at risk of overdose, is an important step to address the synergistic epidemics of suicides and overdose fatalities in the US. The current study assesses whether patterns of suicidality endorsement can indicate risk for substance use and overdose. Methods Latent class analysis (LCA) was used to assess patterns of item level responses to the Concise Health Risk Tracking Self-Report (CHRT-SR), which measures thoughts and feelings associated with suicidal propensity. We used data from 2,541 participants with SUD who were enrolled across 8 randomized clinical trials in the National Drug Abuse Treatment Clinical Trials Network from 2012 to 2021. Characteristics of individuals in each class were assessed, and multivariable logistic regression was performed to examine class membership as a predictor of overdose. LCA was also used to analyze predictors of substance use days. Results Three classes were identified and discussed: Class 1) Minimal Suicidality, with low probabilities of endorsing each CHRT-SR construct; Class 2) Moderate Suicidality, with high probabilities of endorsing pessimism, helplessness, and lack of social support, but minimal endorsement of despair or suicidal thoughts; and Class 3) High Suicidality with high probabilities of endorsing all constructs. Individuals in the High Suicidality class comprise the highest proportions of males, Black/African American individuals, and those with a psychiatric history and baseline depression, as compared with the other two classes. Regression analysis revealed that those in the High Suicidality class are more likely to overdose as compared to those in the Minimal Suicidality class (p=0.04). Conclusions Suicidality is an essential factor to consider when building strategies to screen, identify, and address individuals at risk for overdose. The integration of detailed suicide assessment and suicide risk reduction is a potential solution to help prevent suicide and overdose among people with SUD.